Antibacterial activity of Sireh (Piper betle L.) leaf extracts for controlling bacterial leaf blight diseases in rice plant - Abu Asan, Nor Umaira; Rukayadi, Yaya; Geok, Hun Tan (Malaysian Society for Microbiology, 2022)
Aims: This study aimed to determine the antibacterial activity of Piper betle L. leaf extract against Xanthomonas oryzae pv. oryzae that causes bacterial leaf blight in rice plant. Methodology and results: The antibacterial activity of the P. betle leaf extract (100, 50, 25 and 12.25 mg/mL) with four different solvents (methanol, ethyl acetate, hexane and acetone) was evaluated using a disc diffusion assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values. The inhibition zone of methanolic extract appeared to have the maximum diameter compared to those of other extracts, which is 32.67 mm at a concentration of 100 mg/mL, followed by 30.33 mm, 22.00 mm and 20.30 mm for the concentrations of 50 mg/mL, 25 mg/mL and 12.5 mg/mL, respectively. The MIC and MBC values of the methanolic extract were 0.625 mg/mL suggesting that the extract has a bactericidal effect on X. oryzae pv. oryzae (Xoo). The time-kill curve studies revealed that the 1× MIC (0.625 mg/mL) concentration of methanolic extract had a time and concentration-dependent killing effect on Xoo. Gas chromatography-mass spectrometry (GC-MS) analysis of methanol extract revealed the presence of eugenol acetate (29.53%), 4-allyl-1,2-diacetoxybenzene (29.51%) and 2,3-dimethyl benzoic acid (22.82%) as major compounds. Conclusion, significance and impact of study: The methanolic leaf extract of P. betle was proven to have an effective inhibitory effect on Xoo and may have the potential to be used as an alternative management strategy for controlling rice diseases. In the future study, the methanolic leaf extract of P. betle is one of the recommendations to be applied in glasshouse and field trials.